(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Behaviour of consumers plays a crucial role in marketing the FMCG used by consumers and it depends on various factors. In the current era of globalization, the customer needs and tastes are changing over time. Undeniably, the fast moving consumer goods (FMCG) is contributing high to the growth of Indian GDP. It is necessary for marketers to learn about the factors that are affecting the behaviour of consumers in buying fast moving consumer goods. The main purpose of this paper is to find out the factors that are affecting the buying behaviour of consumers in purchasing fast moving consumer goods. It was found that the behaviour of consumers vary by location, price, promotion, product and physiological factors. However, the effect of these factors affecting the decision of consumers would vary from one product to another.